The Mantodea (Dictyoptera: Insecta) of Rio Grande do Norte, Brazil: First List of Species and Geographical Records - Heleodoro, Raphael Aquino; Agudelo, Antonio; Andreazze, Ricardo (EntomoBrasilis, 2016)
This study presents a list of the mantis species from the Brazilian state of Rio Grande do Norte and their distribution within the state. The records are derived from specimens deposited in the “Adalberto Antonio Varela Freire” Entomological Collection at the Federal University of Rio Grande do Norte. This collection holds a total of 1,816 specimens, representing 30 species distributed in 16 genera distributed in 44 localities. There are two new records to Brazil, 10 to the Northeastern region of Brazil (and Caatinga biome) and 25 to the Rio Grande do Norte. Os Mantodea (Dictyoptera: Insecta) do Rio Grande do Norte, Brasil: Primeira Lista de Espécies e Ocorrências Geográficas Resumo. Este trabalho apresenta a primeira lista de espécies de louva-a-deus do Rio Grande do Norte, bem como sua distribuição dentro do Estado. Os registros das espécies são oriundos de espécimes depositados na Coleção Entomológica “Adalberto Antonio Varela Freire”, localizada na Universidade Federal do Rio Grande do Norte. Essa coleção possui um total de 1.816 espécimes de Mantodea depositados, representando 30 espécies distribuídas em 16 gêneros.